Correlation between Peripheral T Cell Subsets and the Activity of Thyroid-Associated Ophthalmopathy - Hong Hu; Liang Liang; Qian Ge; Xing Jiang; Zhizheng Fu; Chun Liu; Jian Long (International Journal of Endocrinology)
Introduction. Thyroid-associated ophthalmopathy (TAO) is the most common orbital immunological disease in adults. T cells play an important role in the pathogenesis of TAO. However, our knowledge of the circulating T cell subsets in TAO is limited. Objective. To investigate the circulating T cell subsets in TAO and the correlations between them and the activity of TAO. Methods. Thirty-eight TAO patients (19 active and 19 nonactive) were enrolled. The absolute number and percentage of total lymphocytes, CD3+T cells, CD4+T cells, CD8+ T cells, CD3+CD4-CD8-T cells (DNT cells), and CD3+CD4+CD8+ T cells (DPT cells) in peripheral blood were measured by flow cytometer. Results. TAO patients were divided into the active group and the nonactive group by the clinical activity score (CAS). The mean CAS was 4 ± 1.11 in the active group and 1.47 ± 0.61 in the nonactive group. No statistical differences were found in gender, age, and the levels of FT3, FT4, TSH, and TRAb between the two groups. The percentage of DNT cells was lower in the active group than in the non-active group, and it was negatively correlated with CAS (r = −0.349, P=0.032), but not the absolute number. The CD4/CD8 ratio, the absolute number and percentage of CD3+ T cells, CD4+ T cells, CD8+ T cells, and DPT cells did not differ between the two groups. ConclusionIn the present study, we found the percentage of DNT cells was significantly lesser in the active TAO than in the nonactive TAO, and it was negatively correlated with the activity of the TAO. It suggests that DNT cells may involve in the immunopathogenesis of TAO and can serve as a clinical biomarker of the disease activity.